ON THE ESTABLISHMENT AND OPERATION OF THE COORDINATION BODY FOR THE EXTERNAL FINANCIAL CONTROL OF MEGA PROJECTS WITH MIXED PARTICIPATION - A. M. Korolev (Финансы: теория и практика)
To maintain sustainable economic growth and development under the current economic conditions, the government has to ensure large-scale investment activities sufficient for parallel implementation of multiple programs and projects. The so-called mega-projects characterized by high investment costs and providing a long-term multiplier effect on the socio-economic sphere require the biggest efforts and as such are of great significance. At present, both budget funds and money of private investors and lenders may serve as project funding sources. Moreover, in case of mega-projects the distribution of investment risks is needed for which purpose mixed funding schemes are often used when the state takes part in a partial support of the needs of a project, which in turn has a significant positive socio-economic impact. This category of projects is called mega-projects with mixed participation. Today, the main problem in the implementation of mixed participation mega-projects is the overexpenditure caused by an inadequate pre-implementation assessment and inefficient use of financial resources. This necessitates the improvement of the financial control system intended to ensure the achievement of the mega-project targets through the analysis of the project feasibility, effectiveness and legitimacy of procedures of raising and use of money funds. What is more, this category of projects, due to the large number of funding sources, is controlled predominantly by external independent parties, which makes it possible to ensure the transparency in a complicated situation with financial resources. The author examines a possibility of establishing a specialized coordination body to enhance the cooperation of external financial controlling parties involed into a mega-project, improve the efficiency of control and expert-analytical activities through adequate distribution of functional responsibilities between the parties as well as standardize the information flows in the process of running control activities.